2000
DOI: 10.1088/0741-3335/42/3/305
|View full text |Cite
|
Sign up to set email alerts
|

Magnetized vortex tubes in the solar wind plasma

Abstract: We make new applications of our previously proposed method for estimating the strainrate tensor and vorticity vector in plasmas (concerning the local deformation and self rotation of the plasma fluid elements, respectively) solely from magnetic field time series. Here we use solar wind measurements of Ulysses spacecraft made in the outer heliosphere, on and off the ecliptic plane, during the period 1990-1998. The application results imply that the solar wind plasma is, to a good approximation, weakly incompres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…Strauss 1976, Montgomery and Turner 1981, Montgomery 1982, Morrison and Hazeltine 1984, Zank and Matthaeus 1992, Zank and Matthaeus 1993, Bhattacharjee et al 1998. Also, we recently verified, using Ulysses spacecraft magnetic field measurements, that the solar wind plasma is well approximated as being weakly incompressible in the magnetic field normal plane and, additionally, one of the strain-rate tensor eigenvectors is nearly aligned to the local magnetic field, possibly because the magnetic field itself deforms the plasma volume (Polygiannakis and Moussas 1996. As a result, the term (D − (∇ • V )I) • B in the magnetic field induction equation is small compared to the 1 2 ξ × B. Generalizing for any solenoidal field b ideally inducted in a weakly incompressible flow, if…”
Section: Weakly Incompressible and 2d Flowsmentioning
confidence: 52%
See 3 more Smart Citations
“…Strauss 1976, Montgomery and Turner 1981, Montgomery 1982, Morrison and Hazeltine 1984, Zank and Matthaeus 1992, Zank and Matthaeus 1993, Bhattacharjee et al 1998. Also, we recently verified, using Ulysses spacecraft magnetic field measurements, that the solar wind plasma is well approximated as being weakly incompressible in the magnetic field normal plane and, additionally, one of the strain-rate tensor eigenvectors is nearly aligned to the local magnetic field, possibly because the magnetic field itself deforms the plasma volume (Polygiannakis and Moussas 1996. As a result, the term (D − (∇ • V )I) • B in the magnetic field induction equation is small compared to the 1 2 ξ × B. Generalizing for any solenoidal field b ideally inducted in a weakly incompressible flow, if…”
Section: Weakly Incompressible and 2d Flowsmentioning
confidence: 52%
“…with db/dt = ∂b/∂t +(V •∇)b being the field time derivative in the local coordinate system comoving with the lines of flow (often called the Lagrangian, material or substantial derivative). Furthermore, splitting the Jacobian tensor ∇V into symmetric and antisymmetric parts, (1) is equivalently written as (Polygiannakis and Moussas 1996 db dt…”
Section: Induction As Invariance Under Local Convectionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that presence of long-lived organized coherent vortices plays an important role in two-dimensional plasma dynamics. These 2D vortex structures are quite common in space plasmas and were observed in ionosphere (so-called black aurora) (Johnson and Chang, 1995), solar wind (Polygiannakis and Moussas, 2000), the Earth distant magnetotail (Hones et al, 1978) and plasma sheet (Verkhoglyadova et al, 2001). It should be noted that vortex structures were extensively studied in the ionosphere and the magnetosphere of the Earth.…”
Section: Introductionmentioning
confidence: 98%